Tożsamość, samoidentyfikacja, identyfikacja = Identity, self-identification, identification - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is to determine the conceptual scope of the term "identity" and hierarchy of concepts coexisting in speaking of it: self-identification and identification from the point of view of their usefulness in linguistic considerations. In the course of analysis various methodological options, doctrinal stances and premises (mainly of psychology, sociology and linguistics) have been taken into consideration.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie